Grupa Agora – poszukiwanie drogi rozwoju - Ząbkowicz, Jerzy (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
The transformation of Polish society and economy over the last two decades is also reflected in the process of the press market becoming mature. The segments of this market transform assuming a strong market economy character. New dominating players emerge representing both domestic and – increasingly often – foreign capital. The foundation and expansion of the Agora Group, the publisher of „Gazeta Wyborcza” inspires peculiar common interest (or even fascination). It is usually presented rather one-sidedly as a Polish version of an American „rags-to-riches” story. The organizational and financial aspect of the Group operations is usually neglected or oversimplified. This paper was written in the first quarter of 2004. It tries to show the publisher of „Gazeta Wyborcza” not with respect to its media mission but to its economic aspect. The management board of this business outlines and tries to implement a certain strategy. However, in doing so they apparently fail to avoid considerable errors and threats.